Comparison Between Fixed Fluidized Bed (FFB) and Batch Fluidized Bed Reactors in the Evaluation of FCC Catalysts - Passamonti, Francisco Javier (2012)
The laboratory reactors ACE fixed fluidized bed FFB and batch fluidized bed CREC Riser Simulator were compared in the conversion of two commercial vacuum gas oil feedstocks (paraffinic and aromatic types) over two equilibrium commercial FCC catalysts (octane-barrel and resid types) under similar conditions. Reaction temperatures were 510 and 540 ◦C and the catalyst to oil mass ratios were from 4 to 9 in the FFB unit, with time on stream varying from 112 to 50 s, and 6.35 in the CREC Riser Simulator, with reaction times ranging from 5 to 25 s. The results were contrasted in some cases to those of a DCR circulating pilot plant unit at 540 ◦C. When the different product yields were considered, the same catalyst ranking was observed in both laboratory reactors on the whole, differences between catalysts and particularly between feedstocks being more perceptible in the FFB reactor. The CREC Riser Simulator reactor showed a linear yield curve for gasoline, which facilitated the analysis and comparisons; in this case, an overcracking regime was not shown, like in the case of the FFB reactor. The LCO yield curves were more defined and differences between catalysts developed more clearly in the FFB reactor. Coke yields were very high in the FFB reactor, typical of confined beds with continuous feed of the reactants, while in the CREC Riser Simulator reactor they were in the range of those observed in the pilot plant and commercial units. The two laboratory reactors showed complementing potential in the laboratory evaluation of commercial catalysts and feedstocks for the FCC process.